Neuroprotective Effect of Bergamot Juice in 6-OHDA-Induced SH-SY5Y Cell Death, an In Vitro Model of Parkinson's Disease - Nadia Ferlazzo; Santa Cirmi; Alessandro Maugeri; Caterina Russo; Giovanni Enrico Lombardo; Sebastiano Gangemi; Gioacchino Calapai; Vincenzo Mollace; Michele Navarra (MDPI AG, 2020)
Much evidence suggests that both oxidative stress and apoptosis play a key role in the pathogenesis of Parkinson's disease (PD). The present study aims to evaluate the protective effect of bergamot juice (BJ) against 6-hydroxydopamine (6-OHDA)- or H2O2-induced cell death. Treatment of differentiated SH-SY5Y human neuroblastoma cells with 6-OHDA or H2O2 resulted in cell death that was significantly reduced by the pre-treatment with BJ. The protective effects of BJ seem to correlate with the reduction of intracellular reactive oxygen species and nitric oxide generation caused by 6-OHDA or H2O2. BJ also attenuated mitochondrial dysfunction, caspase-3 activation, imbalance of pro- and anti-apoptotic proteins, MAPKs activation and reduced NF-ĸB nuclear translocation evoked by neurotoxic agents. Additionally, BJ exhibited excellent antioxidant capability in cell-free assays. Collectively, our results suggest that BJ exerts neuroprotective effect through the interplay with specific cell targets and its antioxidant activity, making it worthy of consideration for the management of neurodegenerative diseases.